Perubahan dan kehilangan bunyi Arab dalam beberapa bahasa pilihan: satu kajian etimologi bunyi Arab = (changes and loss of Arabic sounds in selected languages: an etimological study on Arabic sounds) - Yeob, Shamsul Jamili; Abdul Rahman, Lubna (Secholian Publication, 2023)
tetapi kebanyakannya telah mengalami perubahan dari segi sebutan Arabnya setelah melalui proses perubahan bunyi (fonetik) asal dalam bahasa tersebut. ABSTRACT Communication across the globe relies primarily on language as the crucial means of expression. Various disciplines of studies, be it professional or non-professional, require language to communication or interact between them and among their fraternity in different areas of interest. Language is also a pertinent and precious asset of a community particularly in developing high civilization and its prosperity. Languages underwent series of developments and processes thousands of years ago where they influenced and were influenced by other languages in a long run, and this is the nature of living language. The study, thus, attempts to unearth the role of Arabic language as one of the most influential languages in the world. The study aims to analize words of a few world languages that are believed to be originated from Arabic word. The study adopts descriptive method to analyze three identified major languages in the world namely: Malay, Chinese and English. The languages are selected based on the number of speakers as well as the native language of the authors. The study focuses on words that contain social meaning only by avoiding any words which semantically incline towards Islamic influence. In addition, it emphasizes also on similar or closer sound to Arabic words as well as changes and loss of Arabic sounds of the analyzed words provided the original Arabic meaning of them is preserved. Giving a concentration on words that contain pronunciational similarity will unveil the similarity of word sound and meaning in Arabic. The study demonstrates that many words of world languages are originated from Arabic words or closely related to them but unfortunately some of them have been influenced by mother tongues or other languages in many ways which resulted to the use of different sounds to facilitate the pronunciation of the original Arabic words in the analyzed languages in particular.